EXPANSION AND THE IMPLICATION OF REGIONAL AUTONOMY IN NORTH SUMATRA - Alinapia Alinapia (Jurnal Dinamika Hukum, 2015)
Region unfoldment euphoria have made Northern Sumatra as one of county unfoldment at Indonesian. For it to need is assessed, how is region unfoldment performing at North Sumatra and its implication to regions autonomous performing at North Sumatra? Method that is utilized is descriptive analytical. That acquired result region unfoldment performing at North Sumatra was appropriate indicator which is determined deep legislation regulation and according to North  Sumatra society expectation. Meanwhile region unfoldment implication to regions autonomous performing, which is region governance (region autonomy) was walking at unfoldment region.Key words: Region Unfoldment performing, Region Unfoldment implication North Sumatra